Support for learning in the perspective of patient safety in primary health care - Thatianny Tanferri de Brito Paranaguá; Ana Lúcia Queiroz Bezerra; Gabriela Camargo Tobias; Suely Itsuko Ciosak
ABSTRACT Objective: to analyze the support for learning, in the perspective of patient safety, offered in the work environment, according to health professionals working in primary care. Method: a transversal study, held with 86 health professionals working in primary care. A validated instrument was used, applied via the Internet. Descriptive statistical analysis was undertaken with a presentation of median, mean, standard deviation and coefficient of variation. Results: points which are favorable to supporting learning were evidenced, such as mutual respect, autonomy for organizing the work and valorization of new ideas, which obtained means above 7.0. The variables which hinder the process of learning in the work environment, perceived by the professionals, were: resistance to changes, and excess of work impeding reflection on how to improve the work, with means above 6.0. Conclusion: the study found evidence of indicators related to the process of staff development in the area of health and indicates the influence of support for learning for the improvement of the work processes and of patient safety. It is necessary that a culture involving the systematic assessment of educational interventions in health should be established, the aim being to diagnose actions which are more incisive for changing health professionals' attitude and, therefore, clinical practice.